Faktor-Faktor yang Mempengaruhi Akuntabilitas Pengelolaan Dana Desa se-Kecamatan Sambi Boyolali - Nia Putri Lestari; Suprihati; LMS Kristiyanti (Nur Science Institute, 2023)
This study aims to determine the influence of village head leadership, competency of village officials and community participation on the accountability of village fund management in an empirical study of villages in the Sambi sub-district. The type of research used in this study was primary data in the form of distributing questionnaires to all village offices in Sambi District. The population in this study were all village officials and BPD (Village Consultative Body) in 16 Village Offices in Sambi District. Sampling used a proportional sampling technique in which the decision was made by taking representatives from each group. Based on the results of the t test on the Village Head Leadership variable, Village Apparatus Competence, and community participation partially affect the Accountability of fund management. Based on the F test it is known that the Leadership of the Village Head, Competence of Village Officials and Community Participation have a simultaneous effect on the Accountability of village fund management in the village